2016
DOI: 10.3390/molecules21050549
|View full text |Cite|
|
Sign up to set email alerts
|

Neuroprotective and Cytotoxic Phthalides from Angelicae Sinensis Radix

Abstract: Seven phthalides, including a new dimeric one named tokinolide C (7), were isolated from Angelicae Sinensis Radix and characterized. The structures of these compounds were elucidated on the basis of comprehensive analysis of spectroscopic data and comparison with literature data. All of the compounds were evaluated for their cytotoxic activities against the A549, HCT-8, and HepG2 cancer cell lines. Riligustilide (4) showed cytotoxicity against three cancer cell lines, with IC 50 values of 13.82, 6.79, and 7.92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Similar structure: free radical scavenging activity (Adil et al 2018), active component of Angelica sinensis (AS) herb, used as the blood-nourishing tonic (Chen et al 2017), anti-inflammatory activity (Tran et al 2018), antioxidant and antibacterial activity against Bacillus subtilis , Staphylococcus aureus , Escherichia coli , Pseudomonas aeruginosa , Klebseilla pneumonia , Agrobacterium tumefaciens and antifungal activity against Candida albicans , Mucor sp., Aspergillus flavus , Penicilium expansum (Ksouri et al 2017), neuroprotective effect on PC12 cells (Lu-Si et al 2017), used to treat bone diseases (Wang et al 2017a, b), prevents cancer by increase the oxygen release efficiency of Hb (Wang and Chen 2017), neuroprotective and anticancer effects against lung (A549), human colon carcinoma (HCT-8), and hepatocarcinoma (HepG2) cancer cell (Gong et al 2016)…”
Section: Resultsmentioning
confidence: 99%
“…Similar structure: free radical scavenging activity (Adil et al 2018), active component of Angelica sinensis (AS) herb, used as the blood-nourishing tonic (Chen et al 2017), anti-inflammatory activity (Tran et al 2018), antioxidant and antibacterial activity against Bacillus subtilis , Staphylococcus aureus , Escherichia coli , Pseudomonas aeruginosa , Klebseilla pneumonia , Agrobacterium tumefaciens and antifungal activity against Candida albicans , Mucor sp., Aspergillus flavus , Penicilium expansum (Ksouri et al 2017), neuroprotective effect on PC12 cells (Lu-Si et al 2017), used to treat bone diseases (Wang et al 2017a, b), prevents cancer by increase the oxygen release efficiency of Hb (Wang and Chen 2017), neuroprotective and anticancer effects against lung (A549), human colon carcinoma (HCT-8), and hepatocarcinoma (HepG2) cancer cell (Gong et al 2016)…”
Section: Resultsmentioning
confidence: 99%
“…It covers 3 meridians, including liver, heart, and spleen. Of course, ASR has been extensively investigated in phytochemistry, 52 - 58 and the results indicated that organic acid (such as ferulic acid), volatile oil (such as senkyunolide I and ligustilide), and polysaccharide are the main components in this plant, which have been proved to be the bioactive compounds of ASR. 59 - 64 Pharmacological studies demonstrated that those components have hematopoietic activity, anti-platelet aggregation, anti-arrhythmic, anti-radiation, anti-tumor, analgesic, regulating smooth muscle and protective effects on organs.…”
Section: Introductionmentioning
confidence: 99%
“…The compound n -Butylidenephthalide (BP) can be isolated from Angelica sinensis —also called dong quai—which is primarily grown in Asia and has major applications in the treatment of anemia and gynecological dysfunction in traditional Chinese medicine [1,2]. Moreover, BP is a natural liposoluble compound with a low molecular weight (188.226 g/mol) that possesses multiple pharmacological activities, such as reducing injury and fibrosis in the liver and neuroprotective activity [3,4,5]. Studies have revealed that BP exerts cytotoxic or inhibitory effects on various cancers, including brain, lung, colon, prostate, and liver cancers [6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%